A Novel Pedicle Screw Placement Surgery Based on Integration of Surgical Guides and Augmented Reality - Kong, Huiyang; Wang, Shuyi; Zhang, Can; Chen, Zan; Wu, Zhanglei; Wang, Jiayu (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Background Augmented reality is a new technology that, when applied to spinal surgery, offers the potential for efficient, safe, and accurate placement of pedicle screws. This study investigated whether augmented reality combined with a guide board improved the safety and accuracy of pedicle screw placement compared to traditional freehand screw placement.Methods Four trainers were divided into augmented reality navigation and freehand groups. Each group consisted of a novice and an experienced spine surgeon. A total of 80 pedicle screws were implanted. First, the AR group reconstructed the three-dimensional (3D) model and planned the screw insertion route according to the computed tomography (CT) data of L2 lumbar vertebrae. Next, the Microsoft HoloLens 2 was used to identify the vertebral model, and the planned virtual path was superimposed on the real cone model. Then, the screw was placed according to the projected trajectory. Finally, Micron Tracker was used to measure the deviation of screws from the preoperatively planned trajectory, and pedicle screws were evaluated using the Gertzbein–Robbins scale.Results In the augmented reality group, the linear deviation of the experienced doctors and novices was 1.59 ± 0.39 and 1.73 ± 0.52 mm, respectively, and the deviation angle was 2.72 ± 0.61 and 2.87 ± 0.63 degrees, respectively. In the freehand group, the linear deviation of the experienced doctors and novices was 2.88 ± 0.58 and 5.25 ± 0.62 mm, respectively, and the deviation angle was 4.41 ± 1.18 and 7.15 ± 1.45 degrees, respectively. The screw placement accuracy rate was 97.5% in the augmented reality navigation group and 77.5% in the freehand group.Conclusions Augmented reality navigation improves the accuracy and safety of pedicle screw implantation compared with the traditional freehand method and can assist inexperienced doctors in successfully completing the surgery.
Keywords: augmented reality; pedicle screw placement; three dimensions; surgery navigation; surgical guide